Clarice Lispector in “Felicidade Clandestina” [Clandestine Happiness]: a Poetics of the Self - Machado Garcia, Lucilene (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article attempts to approximate two planes: reality and fantasy, in the story “Clandestine Happiness” published in the book with the same title. This story narrates the reality of an adult woman who explores childhood fantasies in a time in which she is subjected to cruel games of mockery, that develop to a preocupying level, in a passivity that sometimes reminds the reader of a trapped prey. Nevertheless, the same protagonist who was once subjected to her classmate ́s cunning, now exercises full control in the position of narrator before her readers. She passes from character to constructor of the text, playing with the senses of the reader who is now engaged in the fictional story .